2011
DOI: 10.1007/s00393-011-0765-y
|View full text |Cite
|
Sign up to set email alerts
|

„Treat-to-Target“ (T2T) aus der Sicht der stationären Rheumatologie

Abstract: Publication of the treat-to-target (T2T) concept at the end of the Bone and Joint Decade almost coincided with the 15 treatment recommendations of the EULAR as well as with the new classification and revised remission criteria for rheumatoid arthritis (RA).The treat-to-target initiative is solely focused on the description of benchmarks for an effective treatment management of RA to reach its priority target of remission.From the perspective of inpatient rheumatology parallels are shown to the quality projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Over expression of tumour necrosis factor (TNF) has been shown to play a dominant role in the pathogenesis of various IMIDs, such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), Crohn's disease, ulcerative colitis (UC), psoriasis and psoriatic arthritis (PsA). In addition to evidence from mechanistic studies, pointing out the common pathogenesis and role ofTNF among IMlDs, findings from epidemiological and genetic studies support the theory that IMlDs are related disorders, with a common genetic susceptibility, thus explaining the co-occurrence or 'genetic overlap' and familial patterns of these diseases (2)(3)(4)(5)(6).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Over expression of tumour necrosis factor (TNF) has been shown to play a dominant role in the pathogenesis of various IMIDs, such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), Crohn's disease, ulcerative colitis (UC), psoriasis and psoriatic arthritis (PsA). In addition to evidence from mechanistic studies, pointing out the common pathogenesis and role ofTNF among IMlDs, findings from epidemiological and genetic studies support the theory that IMlDs are related disorders, with a common genetic susceptibility, thus explaining the co-occurrence or 'genetic overlap' and familial patterns of these diseases (2)(3)(4)(5)(6).…”
mentioning
confidence: 75%
“…In addition to evidence from mechanistic studies, pointing out the common pathogenesis and role ofTNF among IMlDs, findings from epidemiological and genetic studies support the theory that IMlDs are related disorders, with a common genetic susceptibility, thus explaining the co-occurrence or 'genetic overlap' and familial patterns of these diseases (2)(3)(4)(5)(6). In addition to evidence from mechanistic studies, pointing out the common pathogenesis and role ofTNF among IMlDs, findings from epidemiological and genetic studies support the theory that IMlDs are related disorders, with a common genetic susceptibility, thus explaining the co-occurrence or 'genetic overlap' and familial patterns of these diseases (2)(3)(4)(5)(6).…”
mentioning
confidence: 84%
“…Among them are the diagnosis-related groups, Pay for Performance (P4P) and CoE that apply the T2T strategy for RA based on PCC model. 33 Previous evidence has shown that involving the patient as an individual with unique needs, concerns and preferences has an important impact on safety, effectiveness and costs. 34 Our results prove that the CoE strategy would have great impact in terms of public policies for the treatment of RA in Colombia.…”
Section: Discussionmentioning
confidence: 99%